1964
DOI: 10.1038/bjc.1964.55
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Tumor Growth

Abstract: IT is commonly believed that tumor growth under ideal conditions is a simple exponential process terminated by the exhaustion of the nutritional support provided by the host. However, a survey of the literature shows that exponential growth of tumors has been observed only rarely and then only for relatively brief periods. When we consider those tumors whose growth has been followed over a sufficiently extensive range (100 to 1000-fold range of growth or more), we find that nearly all such tumors grow more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
485
0
7

Year Published

1965
1965
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 812 publications
(509 citation statements)
references
References 8 publications
17
485
0
7
Order By: Relevance
“…Whilst in the published literature on the growth of human tumours extrapolation has always been by an assumed exponential curve, the availability of more complete data on experimental tumours enables one in principle to make a more sophisticated extrapolation. This has been done by Laird (1964Laird ( , 1965 The Contribution from Studie8 of Cell Proliferation in Tumours Many of the problems in our understanding of the overall growth of tumours arise out of ignorance of the basic characteristics ofthe proliferating cell population, despite the fact that techniques of investigation of cell population kinetics have been developing rapidly over the past ten years (Wimber, 1963). The application of these techniques to experimental tumours has been shown to be feasible and data are now available on a variety of tumour types (Mendelsohn, Dohan and Moore, 1960;Mendelsohn, 1960Mendelsohn, , 1962Bertalanffy and Lau, 1962;Bertalanffy, 1963;Edwards et al, 1960).…”
Section: (Iii) Tumours In Other Sitesmentioning
confidence: 99%
“…Whilst in the published literature on the growth of human tumours extrapolation has always been by an assumed exponential curve, the availability of more complete data on experimental tumours enables one in principle to make a more sophisticated extrapolation. This has been done by Laird (1964Laird ( , 1965 The Contribution from Studie8 of Cell Proliferation in Tumours Many of the problems in our understanding of the overall growth of tumours arise out of ignorance of the basic characteristics ofthe proliferating cell population, despite the fact that techniques of investigation of cell population kinetics have been developing rapidly over the past ten years (Wimber, 1963). The application of these techniques to experimental tumours has been shown to be feasible and data are now available on a variety of tumour types (Mendelsohn, Dohan and Moore, 1960;Mendelsohn, 1960Mendelsohn, , 1962Bertalanffy and Lau, 1962;Bertalanffy, 1963;Edwards et al, 1960).…”
Section: (Iii) Tumours In Other Sitesmentioning
confidence: 99%
“…
RECENTLY we have shown (Laird, 1964) that the growth of a variety of tumors of the mouse, rat and rabbit, whether transplanted or primary, is well described by a Gompertzian equation. Such growth may be regarded as an exponential process limited by an exponential retardation, and tumor growth was therefore interpreted as being due mainly, if not entirely, to an exponential proliferation of tumor cells whose successive mean generation times increase according to an exponential equation.

For the present study, corresponding points on the growth curves of different tumors have been defined, and the growth rates of the tumors compared at these points.

…”
mentioning
confidence: 99%
“…The second case is that of a population growing according to the Gompertz equation, its growth rate decreasing continuously from the start until the population reaches a plateau. This case is typified by a large number of solid and ascitic tumours (Laird 1964(Laird , 1965. The third case is that of a population maintained at a steady-state level by homoeostasis.…”
Section: Dose-response Curves For Agents Thatmentioning
confidence: 99%
“…This principle is illustrated in Fig. 1 Laird (1964Laird ( , 1965 This principle is illustrated in Fig. 2 where it is shown that cells growing at the fastest rate permitted by equation (6) (7), (9) and (10) describe the fates of the three types of population with reference to the fractional reduction F caused by each dose and the interval between doses t. In order to determine the effects of particular regimens we now substitute for F in these equations the expressions in equations (1), (2) Table I gives the equations so derived.…”
Section: Exponentially Growing Populationsmentioning
confidence: 99%
See 1 more Smart Citation